Two new water beetles from the Hantamsberg, an inselberg in the Northern Cape of South Africa (Coleoptera, Hydraenidae) - Bilton, David T. (Zootaxa, 2014)
Mesoceration hantam sp. nov. and Parhydraena faeni sp. nov., are described from the Hantamsberg plateau, an inselberg in the Northern Cape of South Africa. The new species are so far known only from temporary waters on the Hantamsberg summit, where they were both abundant. Sampling in these mountains also revealed an interesting accompanying water beetle fauna, including the northernmost known record of Hydropeplus montanus Omer-Cooper, a species characteristic of mountain fynbos further south in the region.